Usability Testing Payroll System Case Study Gajihub - Stevanoes, Alvian; Dinata, Kevin; Wicaksono, Soetam Rizky (STMIK Amika Soppeng, 2025)
A cloud-based human resource management (HR) application, GajiHub, was launched in Indonesia in 2020 to assist companies in managing personnel administration, especially in the aspect of payroll and employee attendance monitoring. This study aims to evaluate the usability of the main features of the GajiHub application, such as login, employee data input, payroll component settings, salary payments, and promotion management. This study uses the usability testing method with a task-based testing approach, where participants are asked to complete certain tasks on each feature tested. The test results show that most of the features work fine, but some issues related to the user interface and data validation are still found. Recommendations for improvement are proposed to improve the user experience and effectiveness of the application in supporting the company's HR management.